Modelamiento de un transformador óptico de corriente ideal para sistemas de protecciones. - Chasi Alarcón, Klever Santiago (2019)
The present project starts from the theoretical analysis of the measurement and protection transformers, pointing out the advantages that optical technology presents in comparison to the currently equipment used. The Faraday effect in optical fibers is the basis for a new and better technology for electricity measurement over circuits of electric power systems. But only in the last twenty years technology has matured enough to serve as a commercially attractive base for fiber optic sensor applications. The established equations by the physicist Michael Faraday and Malus’ Law at software Matlab are applied, in the modeling the physical whole system effects of an optical current transformer is showed, obtaining as results the mathematical calculations of the angle optical signal alteration and how it is changing in relation to the electricity input, in the same way a graph is displayed where the waves of the light signal and the alterations are exposed and observed in the device, at the same way the behavior of the device is visualized as it can vary its components and their measurements. The established modeling will help the construction of these devices and the calibrations that are made to the Optical CTs.